Characterization of epimerization and composition of heparin and dalteparin using a UHPLC-ESI-MS/MS method. (1st January 2019) - Zhang, Tianji; Liu, Xin; Li, Hongmei; Wang, Zhangjie; Chi, Lianli; Li, Jin-Ping; Tan, Tianwei
Graphical abstract: Highlights: A novel UHPLC-HILIC/WAX-MS/MS approach was applied to characterize HONO depolymerized heparin/dalteparin. Ambiguous disaccharide identification was achieved with unique standards. Isotopic labelling was successfully applied for the sameness evaluation of generic dalteparin. Hexuronic acid epimers were identified by MS/MS/MS (CID and HCD) with LTQ-Orbitrap. Abstract: Heparin is a significant anticoagulant that has been used in clinic over decades. Although numerous efforts have been made to characterize the molecular structure of heparin and its derivatives for safety of the medicine, technical barriers still exist because of their structural complexity. In this study, we have established a method capable to evaluate both the epimerization and composition of heparin and dalteparin by a UHPLC-HILIC/WAX-MS/MS approach. Ten major disaccharide building blocks retaining the epimerization configuration of parental heparin chains were generated and well separated, 9 of which were unambiguously identified. Isomer identifications were achieved through high-resolution tandem mass spectrometry analysis with reference to elaborately prepared standards. The method was successfully applied for the sameness study of generic dalteparins in combination with an isotopic labelling procedure. We believe this robust method maybe adapted to quality control in pharmaceutical production of heparin and LMWHs.